2019
DOI: 10.2147/hmer.s196354
|View full text |Cite
|
Sign up to set email alerts
|

<p>The effect of a mesenchymal stem cell conditioned medium fraction on morphological characteristics of hepatocytes in acetaminophen-induced acute liver failure: a preliminary study</p>

Abstract: Background: In our studies, it was shown that the effectiveness of the conditioned medium obtained by cultivating mesenchymal stem cells depends on the microenvironment conditions used to cultivate the cells. It was demonstrated that the conditioned medium obtained by culturing cells with low oxygen content (10%) has a much more pronounced protective effect. Methods: Protein compositions obtained from MSCs cultured under hypoxic (10% O 2 hc-MSC) and nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…[20] MSC-CM enhances in vitro cell proliferation, [21][22][23] migration, [22,24] angiogenesis, [25] and imparts anti-apoptotic [23,25] and anti-inflammatory [26] effects. In vivo, MSC-CM has demonstrated healing in diverse preclinical indications including cutaneous wounds, [22] Parkinson's disease, [27] liver failure, [28] and myocardial infarction (MI). [29,30] Indeed, significant data indicate that MSC-CM can achieve similar results as direct MSC delivery in various preclinical injury models, [31][32][33] while others report inadequate healing by MSC-CM compared with MSC transplantation.…”
mentioning
confidence: 99%
“…[20] MSC-CM enhances in vitro cell proliferation, [21][22][23] migration, [22,24] angiogenesis, [25] and imparts anti-apoptotic [23,25] and anti-inflammatory [26] effects. In vivo, MSC-CM has demonstrated healing in diverse preclinical indications including cutaneous wounds, [22] Parkinson's disease, [27] liver failure, [28] and myocardial infarction (MI). [29,30] Indeed, significant data indicate that MSC-CM can achieve similar results as direct MSC delivery in various preclinical injury models, [31][32][33] while others report inadequate healing by MSC-CM compared with MSC transplantation.…”
mentioning
confidence: 99%
“…In concordance with all these in vitro data, several in vivo studies showed the advantages of hypoxic pre-conditioning in MSC culture in therapeutic terms. In fact, there are studies reporting that the enhanced paracrine effect of MSC after hypoxic treatment would be beneficial to diabetes [164], liver failure [165,166], irradiation-mediated salivary gland damage [167] or anticancer effects [90]. Nevertheless, despite all these potential therapeutic advantages, there are issues which should be resolved.…”
Section: In Vitromentioning
confidence: 99%
“…MSCs-conditioned medium (CM) could also modify morphological characteristics of hepatocytes in the ALF model. Meanwhile, secretome achieved by cultivating MSCs with low oxygen content (10%) provoked more prominent hepatoprotective influence, and significantly reduced ALT and AST and also pro-inflammatory cytokines serum levels following injection in vivo [ 153 ]. In another study, Li and coworkers evaluated the therapeutic merits of CM from MSCs co-cultured with hepatocytes in the ALF rat model [ 154 ].…”
Section: Mscs-exosome In Alfmentioning
confidence: 99%